2007
DOI: 10.1007/s00441-006-0352-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Jun/Fos protein localization and DNA synthesis in rat adrenal cortex after treatment with ACTH or FGF2

Abstract: In vitro and in vivo studies have suggested that the expression of the early response genes for Jun and Fos proteins plays an important role in adrenal cell proliferation. In order to study the expression pattern of the activating protein-1 (AP-1) family of oncogenes in the adrenal gland, we have used immunohistochemistry to localize Jun and Fos protein expression in rat adrenal cortex infused in situ with adrenocorticotropic hormone (ACTH), fibroblast growth factor 2 (FGF2), or both. The expression of AP-1 fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
5
11
0
3
Order By: Relevance
“…Previous findings from our laboratory have shown that ACTH administration in hypophysectomized (Hyp) or Dextreated rats induces S-phase entry in all zones of the adrenal cortex, which confirms that the adrenocortical proliferative capacity is not restricted to the outer adrenal zone (Baccaro et al 2007;Torres and Lotfi 2007). Moreover, these studies have implicated the AP-1 family of transcription factors in the regulation of the cell cycle during ACTH-induced proliferation in the adrenal cortex .…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…Previous findings from our laboratory have shown that ACTH administration in hypophysectomized (Hyp) or Dextreated rats induces S-phase entry in all zones of the adrenal cortex, which confirms that the adrenocortical proliferative capacity is not restricted to the outer adrenal zone (Baccaro et al 2007;Torres and Lotfi 2007). Moreover, these studies have implicated the AP-1 family of transcription factors in the regulation of the cell cycle during ACTH-induced proliferation in the adrenal cortex .…”
Section: Introductionsupporting
confidence: 70%
“…Conversely, evidence is also available that each zone can be renewed from within itself. Although proliferation is more frequent in the subcapsular/glomerulosa cell zone, it is not restricted to this region, since cell proliferation also occurs in the ZF and ZR (McEwan et al 1999;Baccaro et al 2007;Torres and Lotfi 2007). Additionally, there is evidence that POMC-derived peptides other than ACTH play a role in the control of adrenal growth.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…BaccaroRB, Mendonce PO, Torres TE et al, 2007 found a growth factor FGF responsible for adrenocortical growth in response to stress. 1 According to Viard et al (1994), it was observed that ACTH blocks progression of adrenocortical cells in G1 phase and inhibits DNA synthesis in S-phase, even in the presence of growth factors. After this inhibiting effect, ACTH induces expression of genes associated with cell cycle progression such as C-fos and C-jun.…”
Section: IIImentioning
confidence: 99%
“…This observed difference between techniques may be due to different marked cell populations. The fraction of cell nuclei marked with PCNA is the cell population in late G1, early S phase and DNA synthesis period, while BrDU is only incorporated in cells during DNA synthesis and repairing, offering more precise estimations (Connolly & Bogdanffy, 1993;Baccaro et al, 2007).…”
Section: Discussionmentioning
confidence: 99%